The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7554/elife.61481
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of kinesin inhibition by kinesin-binding protein

Abstract: Subcellular compartmentalisation is necessary for eukaryotic cell function. Spatial and temporal regulation of kinesin activity is essential for building these local environments via control of intracellular cargo distribution. Kinesin binding protein (KBP) interacts with a subset of kinesins via their motor domains, inhibits their microtubule (MT) attachment and blocks their cellular function. However, its mechanisms of inhibition and selectivity have been unclear. Here we use cryo-electron microscopy to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 86 publications
2
38
0
Order By: Relevance
“…Secondarystructure prediction suggested that KBP is built from 19 helices, but clear 'sausage-like' density for only eight helices was observed. Ultimately, the KBP structure was indeed found to have 19 helices as predicted, arranged in a right-handed -solenoid (Atherton et al, 2020). When this final structure was fitted into the KBP density from unsupported ice, eight helices were a good fit, another five fitted poorly and there was missing density for another six (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Secondarystructure prediction suggested that KBP is built from 19 helices, but clear 'sausage-like' density for only eight helices was observed. Ultimately, the KBP structure was indeed found to have 19 helices as predicted, arranged in a right-handed -solenoid (Atherton et al, 2020). When this final structure was fitted into the KBP density from unsupported ice, eight helices were a good fit, another five fitted poorly and there was missing density for another six (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…KBP-KIF15_MD6S or KBP-KIF1A_MD complexes were purified via IMAC using the 6ÂHis tag on the kinesin constructs after incubation with a tenfold excess of KBP, as described previously (Atherton et al, 2020).…”
Section: Protein Expression and Purification For Cryo-emmentioning
confidence: 99%
See 3 more Smart Citations